MODEL MANAJEMEN DATA SPASIAL UNTUK PEMILIHAN JALUR DISTRIBUSI HOLTIKULTURA - Kudang B. Seminar; Mohammad Abousaidi; Agus Wibowo (School of Business, Bogor Agricultural University (SB-IPB), 2005)
One of the primary goals of agroindustry is to deliver horticulture products (vegetables and fruits) to the target marketplaces timely with minimum quality loss. This is vital considering the characteristics of agroproducts particularly vegetables and fruits which are sensitive to the fluctuation of micro- and macroclimate conditions, methods and the duration of delivery. Therefore, the selection of transportation lines for the distribution of agroproducts becomes a determining key to the minimizing of time delay and quality loss in delivering agroproducts to the marketplaces. This demands the support of spatial data that can be utilized to enhance the selection of the best routes for distributing agroproducts. This study discusses the approach of spatial data management to support the decision making for selecting the best transportation lines to deliver horticulture products and demonstrates the implementation issues of the software prorotype for handling the distribution of vegetables in Bogor districts.